(untitled) (Phoenix: International Multidisciplinary Research Journal ( Peer reviewed High Impact Journal ), 2023)
Workplace health psychology is supported and upheld by psychologists, management scientists, sociologists and clinical psychology. Workplace loneliness has become a hot research topic in western occupational health psychology. The research about the spread of employee workplace loneliness in Haryana is lagging behind. As a common negative emotion in workplace, workplace loneliness can bring in a series of negative effects on employees and individuals. At present in Haryana, the transformation of the society and the rapid development of the economy have brought many problems to the workplace. To some extent, these problems will lead to the spreading of the common feeling of loneliness in the workplace. Therefore, it is necessary to study the crisis of workplace loneliness of our employees. At present, the study of loneliness in the workplace is still in its preliminary stage. The main purpose of this paper is to review the main subject of the study of loneliness in the workplace abroad, and to introduce its concepts, dimensions, measurement methods and related research into the country, and provide reference for scholars to study the rising crisis, that is, the sense of loneliness in the workplace.